Formulation, Characterization, and Evaluation of Naringin-Loaded Phytosomal Gel and it’s in vivo Anti-Inflammatory Activity by Carrageenan Animal Model - Kavatagimath, Satish; Mevegar, Aqeeb; Khatib, Nayeem (Indian Journal of Pharmaceutical Education and Research)
Objective: The present study aimed to formulate, optimize, and evaluate a Naringin-loaded phytosomal gel using a 3² factorial design and to assess its anti-inflammatory activity. Materials and Methods: Phytosomes were prepared via the thin-film hydration method using soya lecithin and cholesterol and were characterized for vesicle size, Polydispersity Index (PDI), and entrapment efficiency. Results: Vesicle sizes ranged from 126 to 207.4 nm, with PDI values between 0.119 and 0.312, indicating uniform particle distribution. Entrapment efficiency ranged from 80.08% to 90.66%, with the optimized formulation (F6) exhibiting a vesicle size of 198.9 nm, PDI of 0.236, and the highest entrapment efficiency of 90.66%. This optimized formulation was incorporated into a gel base and evaluated for physicochemical properties, including pH, spreadability, viscosity, and drug content. The Naringin Phytosomal Gel (NG-PH gel) showed a viscosity of 1462±12 cPs and a drug content of 97.18±0.94%. The phytosomal gel demonstrated superior drug diffusion and permeation compared to the plain and standard gels. Skin irritancy tests revealed no erythema or edema, confirming its safety for topical application. Conclusion: Moreover, the phytosomal gel exhibited significant anti-inflammatory activity and maintained stability throughout the study period, highlighting its potential as an effective transdermal delivery system for targeted anti-inflammatory therapy
Keywords: Naringin; Phytosomes; Anti-inflammatory activity; Quality by Design.